Southeast Asian affairs 2014. - Singh, Daljit; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2014)
Contains contributions by experts that discuss the significant issues and events of the year in each of the Southeast Asian nations and the region as a whole.
Imprint varies.
Keywords: Southeast Asia -- Economic conditions; Southeast Asia -- Economic policy; Southeast Asia -- Politics and government; Southeast Asia -- Periodicals